Equity/bond yield correlation and the FED model: evidence of switching behaviour from the G7 markets. Issue 6 (October 2018) - Humpe, Andreas; McMillan, David
Abstract This paper considers how the strength and nature of the relation between the equity and bond yield varies with the level of the real bond yield. We demonstrate that at low levels of the real bond yield, the correlation between the equity and bond yields turns negative. This arises as the lower bond yield implies heightened macroeconomic risk (e.g. deflation and economic stagnation) and causes equity and bond prices to move in opposite directions. The FED model relies on a positive relation for its success in predicting future returns. Thus, we argue that the mixed empirical evidence regarding the FED model arises due to this switch in correlation behaviour. We present supportive evidence for the switching relation and its link to the level of the bond yield using linear and nonlinear smooth transition panel regression techniques for the G7 markets. The results presented here should be of interest to market practitioners who may wish to use the FED model to aid market timing decisions and for academics interested in understanding the interrelations between markets.